School Library Innovation: Barcode Integration in the Laravel Platform at SD IT Adzkia 1 Padang - Meri Azmi; Deddy Prayama; Eno Fitriyanti (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Education is the key to development. The teaching and learning process is crucial in the world of education. Libraries are a trusted source of knowledge. SD IT Adzkia 1 Kota Padang faces challenges in the manual library management, which slows down the borrowing transactions and reporting. The solution offered in this research is to develop a web-based library information system with barcode technology using the Laravel framework and MySQL. This system is designed to facilitate the recording of loans with a barcode scanner. The development method uses the waterfall model with use case, sequence, and entity relationship diagrams. The design and implementation of the system have proven to make data management in the library more efficient. Pendidikan kunci pembangunan. Proses belajar mengajar penting dalam dunia pendidikan. Perpustakaan adalah penyedia sumber ilmu terpercaya. SD IT Adzkia 1 Kota Padang menghadapi tantangan dalam pengelolaan perpustakaan yang manual, memperlambat transaksi peminjaman dan pelaporan. Solusinya yang ditawarkan dalam penelitian ini adalah membangun sistem informasi perpustakaan berbasis website dengan teknologi barcode, menggunakan framework Laravel dan MySQL. Sistem ini dirancang untuk memudahkan pencatatan peminjaman dengan barcode scanner. Metode pengembangannya menggunakan waterfall dengan diagram use case, sequence, dan entity relationship. Dari hasil perancangan dan pembuatan sistem terbukti proses pengelolaan data di pustaka menjadi lebih efisien.